IPO : A Global Guide, Expanded Second Edition - Espinasse, Philippe (Book collections on Project MUSE., 2014)
In this practical guide to initial public offerings, Philippe Espinasse explains the pros and cons of turning private businesses into listed companies. In straightforward, jargon-free language he details the strategies, procedures, and documentation for different forms of listings, and describes the process of marketing and pricing an international IPO. The guide includes many real-life case studies, sample documents, an extensive glossary of terms, and a review of listing requirements for major stock exchanges. It also discusses recent developments in global equity capital markets. This fully revised paperback edition includes additional case studies, information on recent regulatory changes, and new sections on Malaysia and business trusts in Singapore and Hong Kong. IPO: A Global Guide is applicable to any financial jurisdiction, including emerging markets in the Asia-Pacific region, the Middle East, and Eastern Europe. Intended for entrepreneurs, market practitioners and students, this guide will be essential reading for anyone planning to take a company to market.